Analisis Diskursif atas Konfigurasi Wacana Keislaman dan Isu-Isu Islam Kontemporer di Kediri - Hari Widyasmoro; Yuliana Nurul Islami (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2026)
This study examines the typology and characteristics of Islam Nusantara in Kediri by analyzing the configuration of Islamic discourse surrounding contemporary Islamic issues. The study is motivated by the increasing diversity of religious expressions in response to issues such as religious moderation, digital da'wah, religious purification, radicalism, and the relationship between religion and local culture. While previous studies have generally discussed Islam Nusantara as a broad conceptual framework, its diverse typological configurations within specific local contexts remain insufficiently explored. This study therefore aims to identify the typology of Islam Nusantara in Kediri, examine its characteristics, and analyze how different Muslim groups respond to contemporary Islamic issues. Employing a qualitative approach with discursive analysis, this study draws on data collected through interviews, observations, and documentation involving religious leaders, pesantren caretakers, da'wah activists, relevant literature, and digital media. The findings reveal that Islam Nusantara in Kediri is not homogeneous but consists of four major typologies: Integrative Traditionalist Islam, Adaptive Cultural Islam, Progressive Academic Islam, and Popular Digital Islam. These typologies are distinguished by their social bases, intellectual orientations, religious expressions, and strategies for responding to contemporary challenges. The findings further indicate that Islam Nusantara in Kediri is generally characterized by moderation, inclusivity, adaptability, and strong connections to pesantren traditions and local wisdom. This study contributes to the understanding of Islam Nusantara by demonstrating its diverse and dynamic local configurations in response to changing religious, social, cultural, and digital contexts.